Efficacy of Argon Plasma Coagulation Compared with Topical Formalin Application for Chronic Radiation Proctopathy - AA Alfadhli; WM Alazmi; T Ponich; JM Howard; I Prokopiw; A Alaqeel; JC Gregor (Canadian Journal of Gastroenterology)
BACKGROUND: Chronic radiation proctopathy (CRP) is a troublesome complication of radiotherapy to the pelvis for which current treatment modalities are suboptimal. Currently, the application of formalin to the rectal mucosa (AFR) and thermal ablation with argon plasma coagulation (APC) are the most promising options.